Optimalisasi Peran Remaja Masjid Dalam Meningkatkan Kepedulian Sosial Keagamaan Remaja Di Desa Ngrombot Kec. Patianrowo - Masrifatin, Yuni; Rahmawati, Lilis; Setiyawan, Nofika Dwi; Wahyuningtyas, Asfiana; Azmi, Mu’arfatul; Rizqi, Aditya Arum Wijaya (Bisma : Bimbingan Swadaya Masyarakat, 2019)
This article discusses the optimization of the role of mosque teenagers in increasing the social and religious awareness of teenagers in Ngrombot village, Patianrowo subdistrict. The study uses a qualitative approach with data collected through observation, interviews, and document analysis. The results show that the mosque teenagers in Ngrombot village have various activities to increase their social and religious awareness, such as organizing religious events, doing community service, and engaging in religious discussions. The study also found that the mosque teenagers faced several challenges, such as limited resources and the need for better guidance and training. Therefore, the study suggests that the mosque management and community leaders should provide more support, guidance, and resources to empower the mosque teenagers and optimize their role in promoting social and religious awareness among their peers.